Guided self-determination-young versus standard care in the treatment of young females with type 1 diabetes: study protocol for a multicentre randomized controlled trial. Issue 1 (December 2017) - Haas, Josephine; Persson, Martina; Brorsson, Anna; Toft, Eva; Olinder, Anna
Abstract Background Female adolescents with type 1 diabetes mellitus (T1DM) have the most unsatisfactory glycaemic control of all age groups and report higher disease burden, poorer perceived health, and lower quality of life than their male counterparts. Females with T1DM face an excess risk of all-cause mortality compared with men with T1DM. New methods are needed to help and support young females with T1DM to manage their disease. A prerequisite for successful diabetes management is to offer individualized, person-centred care and support the patient's own motivation. Guided self-determination (GSD) is a person-centred reflection and problem-solving method intended to support the patient's own motivation in the daily care of her diabetes and help develop skills to manage difficulties in diabetes self-management. GSD has been shown to improve glycaemic control and decrease psychosocial stress in young women with T1DM. The method has been adapted for adolescents and their parents, termed GSD-young (GSD-Y). The aim of this study was to evaluate whether an intervention with GSD-Y in female adolescents with T1DM leads to improved glycaemic control, self-management, treatment satisfaction, perceived health and quality of life, fewer diabetes-related family conflicts, and improved psychosocial self-efficacy. Methods/design This is a parallel-group randomized controlled superiority trial with an allocation ratio of 1:1. One hundred female adolescents with T1DM, 15–20 years of age, and their parents (if < 18 years of age), will be included. The intervention group will receive seven individual GSD-Y education visits over 3 to 6 months. The control group will receive standard care including regular visits to the diabetes clinic. The primary outcome is level of glycaemic control, measured as glycosylated haemoglobin (HbA1c). Secondary outcomes include diabetes self-management, treatment satisfaction, perceived health and quality of life, diabetes-related family conflicts, and psychosocial self-efficacy. Data will be collected before randomization and at 6 and 12 months. Discussion Poor glycaemic control is common in female adolescents and young adults with T1DM. Long-standing hyperglycaemia increases the risks for severe complications and may also have an adverse impact on the outcome of future pregnancies. In this study, we want to evaluate if the GSD-Y method can be a useful tool in the treatment of female adolescents with T1DM. Trial registration Current controlled trials, ISRCTN57528404 . Registered on 18 February 2015.